A method for modifying the surface density of a graphite boat sheet
By modifying the surface of the graphite boat sheet with polyaminobenzene heterocyclic compound, and using diazotization reaction and phenylenediamine self-reaction to form a dense structure, the problem of powdering and insufficient strength of the graphite boat surface is solved, the surface density and wear resistance are improved, and the stable fixation of the wafer and the uniformity of the coating are ensured.
Patent Information
- Application Number
- CN202411518286.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-10-29
AI Technical Summary
In photovoltaic manufacturing, the wafer fixation is unstable due to surface powdering and insufficient strength, which affects the uniformity of the coating and production efficiency.
The surface modification of the sheet of the graphite boat is carried out by using a solution prepared by polyaminobenzene heterocyclic compound, acid solution, anionic surfactant and nitroso compound, and a dense structure is formed by diazotization reaction and phenylenediamine molecules, thereby enhancing the density of the graphite surface.
The modified graphite boat sheet has a high density on the surface, low degree of powdering, and improved wear resistance. It can fix the wafer more stably, ensuring the uniformity of the coating and production efficiency.
Smart Images

Figure CN119039050B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a core component preparation technology in photovoltaic manufacturing equipment, and in particular to a method for modifying the surface density of a boat sheet of a graphite boat. Background Art
[0002] Graphite boat is a special boat with graphite as the base material. It has the characteristics of high temperature resistance, good chemical stability, high strength, excellent conductivity, etc. It is widely used in electronics, aerospace, military and other fields. In the semiconductor industry, graphite boats are used to manufacture high-temperature furnace tubes, heaters and other equipment; in the solar energy industry, graphite boats are used to manufacture solar panels; in chemical reaction devices, graphite boats are used to carry reactants; in the lithium battery industry, graphite boats are used to manufacture electrode materials, etc. With the continuous development of science and technology, the demand for graphite boats is also gradually increasing.
[0003] There are many kinds of graphite boats for photovoltaic cell production on the market. However, due to the natural layered structure of graphite, it is inevitable that the surface will be powdered, causing pollution to the wafer. At the same time, the surface strength of the graphite boat is low and the wear resistance is poor. After long-term use, the boat sheet of the graphite boat will have a large size deviation, which will affect the fixation of the wafer. When coating, the silicon wafer is easy to move, resulting in uneven coating, affecting the quality and production efficiency of the wafer.
[0004] Traditional improvement methods for the above problems include surface coating, nanoparticle filling and ion beam irradiation technology. Surface coating technology is mostly achieved through physical or chemical means, which is to add coatings such as titanium oxide, silicon carbide, alloys, etc. to the surface of the boat sheet of the graphite boat. However, these coatings have poor conductivity, acid and alkali resistance and high temperature resistance. Nanoparticle filling is to fill nanoparticles (such as oxides, silicon, etc.) into the graphite microstructure to make the particles more tightly filled, enhance its mechanical properties and chemical stability. However, the interaction between nanoparticles and graphite is often insufficient, resulting in a short life of the boat sheet. Ion beam irradiation technology uses ion beams to bombard the graphite surface, so that the surface atoms are rearranged and form a dense structure, but this method is costly, which limits its wide application.
[0005] Therefore, it is urgent to develop a new graphite boat preparation technology to solve the above problems. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for modifying the surface density of a boat sheet of a graphite boat.
[0007] To solve the technical problem, the solution of the present invention is:
[0008] A method for modifying the surface density of a graphite boat sheet is provided, comprising the following steps:
[0009] (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A having a pH value less than 7 (acidic); the polyaminobenzene heterocyclic compound contains at least two amino groups (NH3 - ), and these amino groups (NH3 - ) is directly connected to a benzene ring or a heterocyclic ring;
[0010] (2) Clean the surface of the graphite boat and place it in solution A for 1 to 4 hours to perform the modification reaction;
[0011] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0012] (4) Add solution B to solution A in which the boat is soaked, stir to mix evenly, and then continue to soak for 6 to 12 hours to continue the modification reaction;
[0013] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain the boat sheet for assembling the graphite boat.
[0014] As a preferred embodiment of the present invention, in the solution A, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant is 10:12:0.1-0.3; when the solution B is added to the solution A, the addition amount is controlled so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 7-20:10.
[0015] As a preferred embodiment of the present invention, the polyaminobenzene heterocyclic compound is any one of the following: p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, a phenylenediamine derivative, polyaminobenzene, a polyamino heterocyclic compound, a polyaminobiphenyl compound, polyaminodiphenylamine or polyaminoazobenzene.
[0016] As a preferred embodiment of the present invention, the acid solution is acetic acid, hydrochloric acid, nitric acid or oxalic acid, and its concentration range is 1% to 100% by mass.
[0017] As a preferred embodiment of the present invention, the anionic surfactant is sodium dodecyl sulfate, sodium octadecyl sulfate or sodium dodecyl sulfonate.
[0018] As a preferred embodiment of the present invention, the solvent in the solution A or solution B is deionized water, acetic acid, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc).
[0019] As a preferred embodiment of the present invention, the nitroso compound is sodium nitrite, isopentyl nitrite or tert-butyl nitrite.
[0020] As a preferred embodiment of the present invention, in step (2) and step (4), the temperature for static soaking is 0 to 100°C.
[0021] The present invention also proposes an alternative solution, which is based on the above method, and the immersion process in step (2) and step (4) is replaced by a spraying process, which specifically includes the following operations:
[0022] (a) In step (2), the solution A is contained in a spray device; the solution A is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite piece until it is completely wetted; then the surface is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution A is completely consumed;
[0023] (b) In step (4), the solution B is contained in a spray device; the solution B is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite part until it is completely wetted; then it is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution B is completely consumed.
[0024] Description of the invention principle:
[0025] The invention uses a polyaminobenzene heterocyclic compound as a modified raw material, uses a nitroso compound to diazotize it in an acidic environment, and then utilizes a free radical reaction between a diazo group and graphite to connect the benzene ring to the graphite through a covalent bond; at the same time, a branched tree or chain structure is formed by self-reaction between phenylenediamine molecules during the diazotization process, and its two ends are connected between the graphite sheets, thereby further enhancing the density of the graphite surface and reducing the degree of surface pulverization.
[0026] The schematic diagram and reaction equation of the above surface densification process are attached. Figure 1 Graphite is composed of two-dimensional sheets, and the inter-sheet force is relatively low; this is why graphite has lubricity and the surface is easily pulverized. Through the diazotization reaction, connections are formed between graphite sheets, increasing the inter-sheet force, thereby increasing the surface density and reducing the degree of pulverization.
[0027] In the present invention, the anionic surfactant added simultaneously can promote the reaction of the diazo group with graphite. The soaking reaction is carried out in two stages for the following reasons: in the first stage, the polyaminobenzene heterocyclic compound is more fully in contact with graphite under acidic conditions, infiltrates the graphite surface, and increases the contact area of the reaction; the introduction of nitrite compounds in the second stage can further induce the diazotization reaction of the polyaminobenzene heterocyclic compound and its free radical reaction with graphite. Since the reaction rate of the diazotization reaction is fast, and the polyaminobenzene heterocyclic compound molecules will self-react during the diazotization process; if the polyaminobenzene heterocyclic compound solution is preferentially mixed with the nitrite compound solution, a large amount of precipitation will be produced, which will cause a waste of raw materials and reduce the reactivity with graphite. Therefore, it is necessary to carry out in two steps, and the nitrite compound is introduced in the second stage.
[0028] In the present invention, the soaking process during the modification reaction can also be changed to a spraying process. That is, in two operation steps, the two modification solutions are respectively atomized into fine droplets, so that they are evenly covered on the surface of the graphite part until they are completely wetted, and then the modification reaction is carried out by static treatment. In fact, only a small amount of solution that contacts the graphite surface during the soaking process will participate in the modification reaction; therefore, spraying the solution on the surface can actually play the same role. After repeated verification by the applicant, the final effects of the two modification processes are basically the same.
[0029] Compared with the prior art, the technical effects of the present invention are:
[0030] 1. The present invention utilizes diazotization reaction to modify the boat sheet of the graphite boat, so that the modified boat sheet has the characteristics of high surface density and low powdering degree.
[0031] 2. The raw materials of this process are easy to obtain and the cost is low; the aqueous solvent system has less emissions; the immersion or spraying process is adopted, which is simple to operate and has fewer process flows. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Schematic diagram of graphite boat modified by diazotization reaction. DETAILED DESCRIPTION
[0033] The specific implementation modes of the present invention are described in detail below in conjunction with the accompanying drawings.
[0034] 1. The method for modifying the surface density of a graphite boat sheet of the present invention comprises the following steps:
[0035] (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A having a pH value less than 7 (acidic); the polyaminobenzene heterocyclic compound contains at least two amino groups (NH3 - ), and these amino groups (NH3 -) is directly connected to a benzene ring or a heterocyclic ring;
[0036] As an optional scheme, the polyaminobenzene heterocyclic compound is any one of the following: p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, a phenylenediamine derivative, polyaminobenzene, a polyamino heterocyclic compound, a polyaminobiphenyl compound, a polyaminodiphenylamine or a polyaminoazobenzene. The acid solution is acetic acid, hydrochloric acid, nitric acid or oxalic acid, and its concentration range is 1% to 100% by mass. The anionic surfactant is sodium dodecyl sulfate, sodium octadecyl sulfate or sodium dodecyl sulfonate. The solvent in solution A is deionized water, acetic acid, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc). In solution A, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant is 10:12:0.1 to 0.3;
[0037] (2) Clean the surface of the graphite boat and place it in solution A for 1 to 4 hours to carry out the modification reaction. The temperature of the immersion is 0 to 100°C.
[0038] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0039] As an option, the nitroso compound is sodium nitrite, isoamyl nitrite or tert-butyl nitrite. The solvent in solution B is deionized water, acetic acid, N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) or N,N-dimethylacetamide (DMAc).
[0040] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 7-20:10. Stir to mix the two solutions evenly, and then continue to soak for 6-12 hours to continue the modification reaction, and the soaking temperature is 0-100°C;
[0041] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain the boat sheet for assembling the graphite boat.
[0042] 2. When modifying the surface density of the graphite boat sheet, the modification method can also be adjusted based on the above scheme, and the spraying process can be used instead of the immersion process: specifically, the following operations are included:
[0043] (a) In step (2), the solution A is contained in a spray device; the solution A is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite piece until it is completely wetted; then the surface is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution A is completely consumed;
[0044] (b) In step (4), the solution B is contained in a spray device; the solution B is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite part until it is completely wetted; then it is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution B is completely consumed.
[0045] The present invention is described in detail below with reference to specific embodiments.
[0046] In Examples 1-6, commercially available R8510 graphite boat sheets (made of pure graphite) were used as the surface modification objects.
[0047] Embodiment 1:
[0048] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0049] (1) Prepare a solution A with a pH value of 6 by taking a polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent;
[0050] Among them, the polyaminobenzene heterocyclic compound is p-phenylenediamine, 10g; the acid solution is acetic acid with a concentration of 100% by mass, 12g; the anionic surfactant is sodium dodecyl sulfate, 0.1g; and the solvent is deionized water, 10g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.1;
[0051] (2) Clean the surface of a 3 cm x 3 cm, 1 mm thick graphite boat sample and place it in solution A for 3 hours at a temperature of 0°C.
[0052] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0053] Wherein, the nitroso compound is sodium nitrite, 14 g; the solvent is deionized water, 42 g;
[0054] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 14:10. Stir the two solutions to mix them evenly, and then continue to soak for 12 hours to continue the modification reaction. The soaking temperature is 0°C.
[0055] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0056] Embodiment 2:
[0057] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0058] (1) Prepare a solution A with a pH value of 1 by taking a polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent;
[0059] Among them, the polyaminobenzene heterocyclic compound is 2,6-diaminopyridine, 10g; the acid solution is a hydrochloric acid solution with a concentration of 1% by mass, 12g; the anionic surfactant is sodium octadecyl sulfate, 0.1g; and the solvent is pure acetic acid, 10g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.1;
[0060] (2) Clean the surface of a 3 cm x 3 cm, 1 mm thick graphite boat sample and place it in solution A for 1 hour at a temperature of 25°C.
[0061] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0062] Wherein, the nitroso compound is isoamyl nitrite, 19.6 g; the solvent is pure acetic acid, 42 g;
[0063] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 20:10. Stir the two solutions to mix them evenly, and then continue to soak for 6 hours to continue the modification reaction. The soaking temperature is 25°C;
[0064] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0065] Embodiment 3:
[0066] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0067] (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A with a pH value of 2;
[0068] Among them, the polyaminobenzene heterocyclic compound is 4,4'-diaminobiphenyl, 17.0g; the acid solution is a nitric acid solution with a mass fraction of 10%, 20.4g; the anionic surfactant is sodium dodecyl sulfate, 0.17g; and the solvent is N-methylpyrrolidone, 15g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.1;
[0069] (2) Clean the surface of a 3 cm x 3 cm, 1 mm thick graphite boat sample and place it in solution A for 2 hours at a temperature of 30°C.
[0070] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0071] Wherein, the nitroso compound is tert-butyl nitrite, 20 g; the solvent is N-methylpyrrolidone, 40 g;
[0072] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 12:10. Stir the two solutions to mix them evenly, and then continue to soak for 8 hours to continue the modification reaction. The soaking temperature is 30°C.
[0073] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0074] Embodiment 4:
[0075] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0076] (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A with a pH value of 2;
[0077] Among them, the polyaminobenzene heterocyclic compound is 4,4'-diaminodiphenylamine, 18.4g; the acid solution is oxalic acid solution with a mass fraction of 50%, 22.1g; the anionic surfactant is sodium octadecyl sulfate, 0.36g; and the solvent is N,N-dimethylformamide, 20g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.2;
[0078] (2) Clean the surface of a 3 cm x 3 cm, 1 mm thick graphite boat sample and place it in solution A for 4 hours at a temperature of 50 °C.
[0079] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0080] Wherein, the nitroso compound is isoamyl nitrite, 19.6 g; the solvent is N,N-dimethylformamide, 30 g;
[0081] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 11:10. Stir the two solutions to mix them evenly, and then continue to soak for 10 hours to continue the modification reaction. The soaking temperature is 50°C;
[0082] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0083] Embodiment 5:
[0084] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0085] (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A with a pH value of 2;
[0086] Among them, the polyaminobenzene heterocyclic compound is p-diaminoazobenzene, 19.6g; the acid solution is 80% acetic acid solution, 23.5g; the anionic surfactant is sodium octadecyl sulfate, 0.58g; the solvent is N,N-dimethylacetamide, 20g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.3;
[0087] (2) Clean the surface of a 3 cm x 3 cm, 1 mm thick graphite boat sample and place it in solution A for 3 hours at a temperature of 100 °C.
[0088] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0089] Wherein, the nitroso compound is sodium nitrite, 14g; the solvent is N,N-dimethylacetamide, 40g;
[0090] (4) Add solution B to solution A in which the boat is soaked, and control the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 7:10. Stir the two solutions to mix them evenly, and then continue to soak for 12 hours to continue the modification reaction. The soaking temperature is 100°C.
[0091] (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0092] Embodiment 6:
[0093] In this embodiment, the method for modifying the surface density of a graphite boat sheet comprises the following steps:
[0094] (1) Prepare a solution A with a pH value of 6 by taking a polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent;
[0095] Among them, the polyaminobenzene heterocyclic compound is p-phenylenediamine, 10.0g; the acid solution is acetic acid with a concentration of 100% by mass, 12.0g; the anionic surfactant is sodium dodecyl sulfate, 0.1g; and the solvent is deionized water, 10g. That is, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant in solution A is 10:12:0.1;
[0096] (2) Clean the surface of a 3 cm × 3 cm, 1 mm thick graphite boat sample, and use a compressed air sprayer (model SUE18B) to evenly spray solution A on the surface of the graphite part to completely wet the surface. Let it stand for 1 h. Repeat the spraying after the surface is dry until solution A is completely sprayed on the surface of the graphite part.
[0097] (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B;
[0098] The nitroso compound is sodium nitrite, 14 g; the solvent is deionized water, 42 g; the amount of solution B prepared is controlled so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 14:10;
[0099] (4) Use a compressed air sprayer (model SUE18B) to evenly spray solution B on the surface of the graphite part to completely wet the surface and let it stand for 1 hour; after the surface is dry, repeat the spraying until all the parts are sprayed;
[0100] (5) Rinse the boat sheet with deionized water and dry it to obtain a boat sheet sample for assembling a graphite boat.
[0101] Comparative Example 1:
[0102] A commercially available graphite boat of model R8510 was used as comparative example 1, and the boat was not subjected to surface modification treatment.
[0103] Product testing and result analysis:
[0104] 1. The modified product of the embodiment of the present invention and the unmodified graphite boat sheets and the graphite boat sheets modified by the prior art in Comparative Examples 1-4 were tested respectively. The test results are shown in Table 1.
[0105] The surface density and electrical conductivity are measured in accordance with GB / T 20042.6-2024 standard; the surface powdering degree is measured in accordance with GB / T1766-2008 standard.
[0106] Table 1 Comparison of air tightness before and after plugging
[0107]
[0108] From the data in Table 1, it can be seen that the conductivity of the graphite subjected to surface densification treatment in Examples 1-6 of the present invention is generally greater than 850 S / cm, which is equivalent to pure graphite. Since the diazotization reaction starts from the surface of graphite first, the dense structure formed will hinder the nitroso compound from further entering the graphite interior for reaction, so most of the reaction occurs only on the surface of graphite (no more than 1mm depth), and the formed cross-linked structure is distributed between graphite flakes / particles, so the surface treatment of the present invention has no effect on the overall mechanical properties and surface roughness of graphite. Since the present invention utilizes the structural densification effect of the free radical reaction of diazo groups with graphite and the self-reaction between phenylenediamine molecules during the treatment process, the self-reaction products between phenylenediamine molecules are filled between the graphite flakes / particles. Therefore, the modification treatment of the present invention can reduce the surface porosity of the product by more than 65%, the outer layer density (taking a thickness of 10μm) is increased from 1.85 of the boat sheet without surface modification treatment to more than 2.1, and the surface powdering degree is reduced by more than 80%.
[0109] In summary, the modification treatment of the present invention does not affect the product size and precision, nor does it affect the surface roughness; the modified boat sheet has the characteristics of high surface density, low powdering degree, and high wear resistance. Based on the above technical advantages, this method can also be widely used in graphite products in various precision machining fields.
[0110] It should be noted that the above embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. For those of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
Claims
1. A method for modifying the surface density of a graphite boat sheet, characterized in that: The following steps are involved: (1) A polyaminobenzene heterocyclic compound, an acid solution, an anionic surfactant and an appropriate amount of solvent are prepared into a solution A having a pH value of less than 7; the polyaminobenzene heterocyclic compound contains at least two amino groups, and these amino groups are directly connected to the benzene ring or the heterocyclic ring; the polyaminobenzene heterocyclic compound is any one of the following: p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, a phenylenediamine derivative, a polyamino heterocyclic compound, a polyaminobiphenyl compound, a polyaminodiphenylamine or a polyaminoazobenzene; in the solution A, the mass ratio of the polyaminobenzene heterocyclic compound, the acid solution and the anionic surfactant is 10:12:0.1-0.3; (2) Clean the surface of the graphite boat and place it in solution A for 1 to 4 hours to perform the modification reaction; (3) Take a nitroso compound and an appropriate amount of solvent to prepare solution B; (4) adding solution B to solution A in which the boat is soaked, stirring to mix evenly, and then allowing the mixture to stand for 6 to 12 hours to continue the modification reaction; when adding solution B to solution A, controlling the amount of solution B added so that the mass ratio of the nitroso compound to the polyaminobenzene heterocyclic compound is 7 to 20:10; (5) Take out the boat sheet, rinse it with deionized water, and dry it to obtain the boat sheet for assembling the graphite boat.
2. The method according to claim 1, characterized in that The acid solution is acetic acid, hydrochloric acid, nitric acid or oxalic acid, and its concentration range is 1% to 100% by mass.
3. The method according to claim 1, characterized in that: The anionic surfactant is sodium dodecyl sulfate, sodium octadecyl sulfate or sodium dodecyl sulfonate.
4. The method according to claim 1, characterized in that The solvent in the solution A or solution B is deionized water, acetic acid, N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide.
5. The method according to claim 1, characterized in that: The nitroso compound is sodium nitrite, isopentyl nitrite or tert-butyl nitrite.
6. The method according to claim 1, characterized in that In the steps (2) and (4), the temperature for static soaking is 0 to 100°C.
7. A method for modifying the surface density of a graphite boat sheet, characterized in that: Based on the method described in any one of claims 1 to 6, the immersion process in step (2) and step (4) is changed to a spraying process, which specifically includes the following operations: (a) In step (2), the solution A is contained in a spray device; the solution A is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite piece until it is completely wetted; then the surface is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution A is completely consumed; (b) In step (4), the solution B is contained in a spray device; the solution B is atomized into fine droplets by compressed gas and then evenly covered on the surface of the graphite part until it is completely wetted; then it is allowed to stand for 1 hour to carry out the modification reaction; after the surface is dry, the spraying operation and the standing treatment are repeated until the solution B is completely consumed.
Citation Information
Patent Citations
Graphene coating and preparation method of graphene conductive corrosion-resistant coating
CN112341848A
Graphite surface diazotization grafted phenol layer-based modified graphite electrode and preparation method thereof
CN115172664A